The adverse consequences of quantitative easing (QE): international capital flows and corporate debt growth in China - Maiani, Stefano; Lamla, Michael; Wood, Geoffrey; Yvonne, Ehrstein (Oxford University Press, 2024)
The economic institutionalist literature often suggests that sub-optimal institutional arrangements impart unique distortions in China, and excessive corporate debt is a symptom of this condition. However, lax monetary policies after the global financial crisis, and specifically, quantitative easing have led to concerns about debt bubbles under a wide range of institutional regimes. This study draws on data from Chinese listed firms, supplemented by numerous macroeconomic control variables, to isolate the effect of international capital flows from other drivers of firm leverage. We conclude that the rise in, and distribution of, Chinese corporate debt can partly be ascribed to the effects of monetary policy outside of China and that Chinese institutional features amplify these effects. Whilst Chinese firms are affected by developments in the global financial ecosystem, domestic institutional realities and distortions may unevenly add their own particular effects, providing further support for and extending the variegated capitalism literature.
Keywords: variegated capitalism; debt bubbles; international capital flows; monetary policy; quantitative easing; fixed-effects regression; regulation